Facets of Consumer Behavior Management: Reflexes and Neurointerface (Global Journal of Management and Business Research, 2023)
The Internet social networks cloud services and e-commerce have rapidly become important components of modern human life However recent studies of neurotechnological companies have marked the foreseeable transition of civilization from the stage of information development to cyber-physical systems that combine the real analog world and cyberspace The scientific novelty and purpose of this study is due to the lack of a holistic study of the evolution of the theory of behavioral design in world science The scientific novelty and purpose of this study is due to the lack of a holistic study of the evolution of the theory of behavioral design in world science The interdisciplinary approach is the main method of research on the basis of which the integration of data tools techniques concepts of physiology psychology neurobiology addictology sociology computer science cybernetics captology political science economics ethics is carried out The concept of behavioral design has emerged and is developing as a synthesis of the ideas of the physiological theory of reflexes and reinforcement the psychoanalytic theory of crowds and operational conditioning theories of public opinion management and organizational change institutional concepts of consumer behavior computerization and development of data networks neurobiology and artificial intelligence In foreign practice behavioral design is used in digital devices architecture in the processes of reducing crime protecting against errors in the organization of processes in healthcare creating energy-saving resource-saving and eco- friendly products solving problems with coronavirus reducing unproductive screen time creating virtual products for healthcare education social security Neurocomputer interface technologies will not replace but will complement digital behavioral design with new tools will lead to the formation of the next generation of a wide range of new specific needs and ways to meet them However the neurointerface can both contribute to reducing the risks of artificial intelligence for humanity and can be used by neurotechnological companies for destructive purposes The theoretical and empirical significance and the need to reorient behavioral design research from the field of business development to the field of consumer protection the development of healthy behavior ethical approaches are obvious
Keywords: behavioral design; neurointerface; cyberphysical systems; addictive design; captology; digital goods; neuroethics